IDENTIFIKASI ANTAGONIS DARI Xanthomonas campestris YANG DIISOLASI DARI RHIZOSPHERE PERKEBUNAN BROKOLI (Brassica oleracea var. italica) DI DESA KEMBANG MERTA, KABUPATEN TABANAN, BALI - Wulansari, Nadya Treesna; Ramona, Yan; Proborini, Meitini Wahyuni (Metamorfosa: Journal of Biological Sciences, 2015)
The main objectives of this research were to isolate and identify antagonists of Xanthomonas campestris from rhizosphere zone of broccoli plants. Soil samples were collected from broccoli farm located at Kembang Merta village, Tabanan, Bali. Isolation and identification of the antagonists were conducted at the Laboratory of Microbiology, Udayana University. Two fungal ( Trichoderma harzianum and  Trichoderma viride ) and two bacterial ( Bacillus sp. and Pseudomonas sp.) antagonists potentially to be developed as biocontrol agents of Xanthomonas campestris were successfully identified in this research.
Keywords: Broccoli, Trichoderma harzianum, Trichoderma viride, Bacillus sp., Pseudomonas sp., Bali